GAMBARAN PEMERIKSAAN ANTENATAL CARE (ANC) DI ERA PANDEMI COVID 19 DI WILAYAH KERJA PUSKESMAS BAAMANG II TAHUN 2020 - herli gustiani (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2022)
Background : Antenatal care check up according to standards are currently constrained by the Covid-19 outbreak which on March 11, 2020 was designated by WHO as a pandemic. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) better known as the Corona virus is a new type of coronavirus that is transmitted to humans. Based on data from the Covid-19 Handling Acceleration Group in 2020, as many as 4.9% of pregnant women were confirmed to have Covid-19. Based on a preliminary study conducted by researchers at the Baamang II Health Center in March - August 2021 by looking at medical records or register books and interviews with the Coordinator Midwife in the MCH Room that the number of pregnant women who performed ANC examinations on Visit 1 (K1) was 673 people and 4 (K4) as many as 644 people in the era of the Covid-19 pandemic in 2020. Research Objectives : To find out the description of Antenatal Care (ANC) Check Up in the Era of the Covid-19 Pandemic in the Work Area of ??the Baamang II Health Center in 2020. Research Methods : This study used an analytic method with a retrospective approach and a cross sectional research design. Which was carried out at the Baamang II Sampit Health Center in July - August 2020 with a sample of 87 people using a random sampling technique from secondary data. This study uses a single variable where the main variable is ANC check up in the Covid 19 pandemic era and the sub variables are K1, K2, K3, K4, SOP for ANC services in the Covid 19 pandemic era. Research result : The results of this study used univariate analysis and crosstab analysis. As many as 87 respondents (100%) on Visit 1, Visit 2, Visit 3, and Visit 4 at Baamang II Health Center in 2020. ANC check up was carried out for BB measurements as many as 87 Body Temperature Screening was carried out for 87 respondents (100%), Screening of Contact History with Patients Confirmed with Covid 19 as many as 12 respondents (13.8%) ), Travel History Screening as many as 7 respondents (8%), the use of PPE as many as 87 respondents (100%) at Visit 1, Visit 2, Visit 3, Visit 4 at the Baamang II Health Center in 2020. Conclusion : Antenatal Care (ANC) check up in accordance with Standard Operating Procedures for ANC services in the Covid 19 Pandemic Era in the Baamang II Sampit Health Center Work Area in 2020. Keywords : ANC check up in the era of the Covid 19 pandemic